2012
DOI: 10.1111/j.1530-0277.2012.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Among Pregnant Women in a Swedish Sample and Its Effects on the Newborn Outcomes

Abstract: The AUDIT questionnaire and 2 specific alcohol biomarkers were used in routine maternity care to collect information about drinking during pregnancy and thereby to identify children at risk for alcohol-related complications. While the AUDIT results suggested that a significant number of women continued using alcohol during pregnancy, implying a risk for fetal disorders, the biomarkers showed negative test values thus indicating only modest drinking levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
4
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 42 publications
(60 reference statements)
3
60
4
11
Order By: Relevance
“…Women who rarely or never drank alcohol had little or nothing to change. This result challenges findings from several studies [36] [45]- [47], including a systematic review [48] showing that predictors most positively associated with alcohol use during pregnancy are pre-pregnancy alcohol consumption, higher maternal age, and previous children. The argument is that behavioral patterns established prior to pregnancy are difficult to alter, and more difficult the longer they have been present [11].…”
Section: Discussioncontrasting
confidence: 54%
“…Women who rarely or never drank alcohol had little or nothing to change. This result challenges findings from several studies [36] [45]- [47], including a systematic review [48] showing that predictors most positively associated with alcohol use during pregnancy are pre-pregnancy alcohol consumption, higher maternal age, and previous children. The argument is that behavioral patterns established prior to pregnancy are difficult to alter, and more difficult the longer they have been present [11].…”
Section: Discussioncontrasting
confidence: 54%
“…10,20,23,24 This may be the result of less access to information and greater propensity to behaviours associated with alcohol consumption, including tobacco smoking and illicit drug use. It has also been found that the prevalence of alcohol intake among tobacco smokers is twice that found among non-smokers 25,26 and up to five times higher among illicit drug users, thus providing evidence that these are behaviours associated with alcoholic drink intake. 19,21 According to the literature, self-reported depression increases the likelihood of alcohol use as mental morbidities are commonly associated with the use of substances such as alcohol, cigarettes and other illicit drugs.…”
Section: Discussionmentioning
confidence: 88%
“…In the Western Cape Province, approximately 34% of women who reside in urban areas, and 41%-51% of women who live in rural areas, consume alcohol during pregnancy (Croxford & Viljoen, 1998;1999). This is vastly greater than the percentages of pregnant women who drink alcohol in either the United States (10%) or Sweden (12%) (Comasco, Hallberg, Helander, Oreland, & Sundelin-Wahlsten, 2012;Havens, Simmons, Shannon, & Hansen, 2009).…”
Section: Why Are Fasd Rates Highest In Western Cape Province South Amentioning
confidence: 87%